Video-assisted thoracoscopic surgery right upper posterior segmentectomywith systemic mediastinal lymph node dissection - Ma, Lin (J Thorac Dis, 2014)
Video-assisted thoracoscopic surgery (VATS) segmentectomy is a promising treatment option for rigorously selected patients with earlystage non-small cell lung cancer. In the presented video, a 66-year-old male with a 1.6 cm suspicious nodule located at the posterior segment of the right upper lobe was treated with anatomic segmentectomy and systemic mediastinal lymph node (LN) dissection successfully.